Evaluation of heat stress indicators in the main locations of intensive dairy production in Lima, Peru - Felipe Ruiz G., Luis (2019)
The aim of this study was to evaluate heat stress indicators in the main locations of intensive dairy production of the department of Lima. The localities of Végueta, Huacho, Huaral, Lurín and Cañete were evaluated during the period 2010-2013. The monthly and local average of air temperature, relative humidity and temperature-humidity index, the duration of the heat stress and the heat overload index (ITH Overload) were calculated. The percentage of days in which ITH Overload was greater than 0 and the percentage of days according to severity of heat stress were calculated. It was showed that the ITH Overload was greater than 10 from November to May, with a peak in February. The duration of the heat stress was greater than 12 hours between January and April. Cañete was the location with the highest ITH Overload and longest duration of heat stress. The cows in Vegueta suffered some degree of heat stress in 98% of the days of the year. The severity of heat stress by location was Cañete > Végueta > Huacho > Huaral > Lurín. It is concluded that dairy cattle in the Lima area are subjected to heat stress during most of the year, being the area of Cañete the most affected.